Will you marry me? It depends (on the business cycle) - Héctor Bellido; Miriam Marcén (Global Labor Organization (GLO), 2018)
This paper studies the effect of the business cycle on the marriage rate, using a panel data of 30 European countries covering 1991 to 2013. We find a negative effect of the business cycle on the marriage rate, pointing to the pro-cyclical behaviour of marriage decisions, which holds after controlling for country-level specific characteristics and family law, and after taking possible endogeneity problems into account. We also analyse this issue considering a wide range of country-level regulations affecting couples (taxation, property division, and reproduction, among others). Supplemental analysis reveals gender differences in the impact of the business cycle on the marital decision, depending on the previous legal marital status of the individuals.
Keywords: J12; J64; 330; Marriage; unemployment; business cycle